Characterising Hidden Defects in GFRP/CFRP Composites by using Laser Vibrometry and Active IR Thermography; Nondestructive Testing and Evaluation; Vol. 37, iss. 6 - Derusova D. A. Dariya Aleksandrovna; Vavilov V. P. Vladimir Platonovich; Shpilnoy V. Yu. Viktor Yurjevich; Siddiqui A. O. Ahmad; Prasad Y. L. V. D.; Druzhinin N. V. Nikolay Vladimirovich; Zhvyrblya V. Yu. Vadim Yurievich (2022, 2022)
Title screen